IMPROVING FINANCIAL SUPPORT SYSTEMS FOR INNOVATIVE OPERATIONS IN TEXTILE ENTERPRISES - Samaroxonov Asqarxon Jamolxon oʻgʻli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Innovation has become a key driver of competitiveness and long-term sustainability in the textile industry. However, access to adequate and effective financial support remains a major constraint for many textile enterprises, particularly in developing economies. This article explores the challenges associated with financing innovative activities in textile firms and proposes strategic directions to improve financial support systems. The study emphasizes the role of internal and external financing sources, public-private partnerships, government incentives, and financial risk management in enhancing innovation capabilities in the textile sector.